Single phase cascaded multilevel inverter / Jefri Adnan - Adnan, Jefri (2009)
The emergence of multilevel converter has become attractive in the power industries and it is suitable in many applications due to their ability to synthesize waveforms with better harmonic spectrum. This paper presents the single phase cascaded multilevel inverter with 11 levels output. This project's objectives are to build the single phase cascaded multilevel inverter model and to get the steps output waveform which the voltage will boost according to the number of level and lastly to investigate its performance in term of harmonics. Software simulation which is used in this project is by using MATLAB/SIMULINK. The switching method that used to control IGBT switches is by using SPWM method. The simulation results are reported and discussed.